Topological photonic crystal composite structure for realizing one-way transmission of light waves based on energy band inversion - ZHU XIAODONG; LIU XIN; YANG YIBIAO; LI XUEMEI; CAO BINZHAO; ZHANG MINGDA; FEI HONGMING (2020)
The invention belongs to quantum optics and optical communication systems, and particularly relates to a topological photonic crystal composite structure for realizing one-way transmission of light waves based on energy band inversion. A topological photonic crystal composite structure for realizing unidirectional transmission of light waves based on energy band inversion comprises two kinds of two-dimensional photonic crystals PhC1 and PhC2 with the same crystal lattice and the same type, and unidirectional transmission of light is realized on an interface of the two kinds of two-dimensionalphotonic crystals. According to the invention, the structure can realize unidirectional transmission of TM mode light, is immune to defects and impurities, and can provide a new thought for designinga novel optical waveguide for an efficient optical transmission problem. 本发明属于量子光学和光通信系统，具体涉及一种基于能带反转实现光波单向传输的拓扑光子晶体复合结构。一种基于能带反转实现光波单向传输的拓扑光子晶体复合结构，该结构包括两种相同晶格、类型相同的二维光子晶体PhC1与PhC2，光在两种二维光子晶体的分界面上实现单向传输。本发明提供了一种基于能带反转实现光波单向传输